The problems faced by Saudi students on scholarship who are studying in American universities - Farah, Mona Ibrahim (Journal of Humanities & Social Sciences, 2020)
The study aimed at identifying the problems faced by Saudi students on scholarship who are studying in American universities. A descriptive method was used and an electronic questionnaire was selected to collect data. The sample size of this study was 226 students. The results revealed that academic problems ranked first where half of the sample agreed that the length of the administrative procedures for the students' transactions in the mission caused them academic problems, followed by the low skills of some students in the English language which represent a hindrance to passing the language test to join the American universities. The other complication was the provided list of distinguished universities, which caused the students to face difficulties to obtain university admission. The economic problems ranked second. The main concern included; "I was forced to deprive myself of the things I love because of my limited income", followed by the difficulty of balancing between the necessary needs and the amount of the monthly allowance, followed by their monthly expenses which exceeded the amount of allowance they receive. Social problems ranked third, the most important of which was the difficulty of studying during the month of Ramadan away from the family, followed by difficulties of social interaction with the local population, and the feeling of alienation in the country of scholarship. The results showed that there were statistically significant differences among the sample according to the age variable, and their monthly income in the social problems they face. The result also indicated that the source of the monthly income showed a difference statistically in their economic problems. The study major variable also showed statistically significant differences in academic problems.
Keywords: social problems; academic problems; economic problems; academic scholarship; universities